2011
DOI: 10.1364/ol.36.003957
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of light from particles with semisoft boundaries

Abstract: A three-dimensional multi-Gaussian function, being a finite sum of Gaussian functions, is adopted for modeling of a spherically symmetric scatterer with a semisoft boundary, i.e. such that has continuous and adjustable drop in the index of refraction. A Gaussian sphere and a hard sphere are the two limiting cases when the number of terms in multi-Gaussian distribution is one and infinity, respectively. The effect of the boundary's softness on the intensity distribution of the scattered wave is revealed. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…(15) must be negligible Figure 3 shows several typical far fields radiated by the source in Eq. (9). It is clearly seen that a beam with a Gaussian degree of coherence (M 1) in the source plane monotonically decreases with the increase of angle θ, while beams with multi-Gaussian source correlations have flat profiles with different heights and steepness of the edges.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…(15) must be negligible Figure 3 shows several typical far fields radiated by the source in Eq. (9). It is clearly seen that a beam with a Gaussian degree of coherence (M 1) in the source plane monotonically decreases with the increase of angle θ, while beams with multi-Gaussian source correlations have flat profiles with different heights and steepness of the edges.…”
mentioning
confidence: 92%
“…Such functions have previously been employed for modeling of beams [8] and scattering potentials [9]. Generally, the multi-Gaussian functions make it possible to control the width of the flat center of the beam intensity profile and the slope of its edge by the choice of two parameters.…”
mentioning
confidence: 99%
“…Pairstructure matrix is responsible for taking into account correlations between particles of the same and different types. b) other [35], [44], [49] The weak scattering theory was extended from scalar to electromagnetic domain in [35]. This development made it possible to predict how polarization properties of incident waves are modified on scattering, in the most general case, when both the source and the scatterer are of random nature.…”
Section: Scattering Of Stochastic Fieldsmentioning
confidence: 99%
“…An inverse problem of finding an unknown position of a particle embedded into random collection of other particles is solved via making a set experiments [44]. Scattering of fields from particles with semi-soft boundaries was considered in [49]. The particles with potentials that can adjust hardness has been modeled with the help of the multi-Gaussian functions, i.e.…”
Section: Scattering Of Stochastic Fieldsmentioning
confidence: 99%
“…This phenomenon may provide a method for the determination of the structure characters from the measurements of the scattered spectrum. Recently, a new model, that is, the semisoft boundary model, was presented [14] . It is found that when a scalar light wave is scattered from a semisoft boundary medium, not only spectral shifts but also spectral switches can be produced in the far-zone scattered field [15] .…”
mentioning
confidence: 99%